2017
DOI: 10.3390/molecules22020220
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal Activity of Quinoxaline 1,4 Di-N-oxide Derivatives as Trypanothione Reductase Inhibitors

Abstract: Chagas disease or American trypanosomiasis is a worldwide public health problem. In this work, we evaluated 26 new propyl and isopropyl quinoxaline-7-carboxylate 1,4-di-N-oxide derivatives as potential trypanocidal agents. Additionally, molecular docking and enzymatic assays on trypanothione reductase (TR) were performed to provide a basis for their potential mechanism of action. Seven compounds showed better trypanocidal activity on epimastigotes than the reference drugs, and only four displayed activity on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…Improving selectivity in drug design is a must. Thus, from the series of BTA’s compounds attained, it was important to determine whether their biological activity was a consequence of being selective or due to their general toxicity [23]. Thus, results from the experiments showed that in the case of compounds 3f and 3g their trypanocidal effect is due to toxicity and not to selectivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving selectivity in drug design is a must. Thus, from the series of BTA’s compounds attained, it was important to determine whether their biological activity was a consequence of being selective or due to their general toxicity [23]. Thus, results from the experiments showed that in the case of compounds 3f and 3g their trypanocidal effect is due to toxicity and not to selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…The quantification of bloodstream trypomastigotes was performed by the Brener-Pizzi method, 5 μL of blood was deposited between a slide and a coverslip (18 × 18 mm), and all bloodstream trypomastigotes present in 20 fields were quantified in an optical microscope at 40×. The amount of trypomastigotes from each sample was compared to the negative control and the percentage of lysis was determined; finally, the lytic concentration of 50% parasites (LC 50 ) were calculated for each compound and converted to micromolar data [23].…”
Section: Methodsmentioning
confidence: 99%
“…Trypanothione reductase, an example of a sulphur-modulated protein in the St phase, was found to have its activity inhibited for propyl and isopropyl quinoxaline-derivatives, as was recently established in T . cruzi , making it a potential drug target 18 . Another sulphur-modulated protein is thiol-dependent reductase 1, which is implicated in deglutathionylation and activation of the antimonial drugs used for treating leishmaniasis 19 .…”
Section: Discussionmentioning
confidence: 99%
“…All compounds from the methyl, ethyl, isopropyl, and n-propyl ester series of quinoxaline 1,4- N -oxide were obtained following the procedure previously reported by Gomez-Caro et al [ 20 ]. These compounds were analyzed by IR, 1 H-NMR and elemental analysis and have been previously reported [ 21 , 22 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%